A Note on Norwegian Forestry - Muthoo, M. K. (Indian Forester, 1958)
Although partly attributable to the varying circumstances in Norway and India (viz., the low population, better transport facilities and cheap electricity, etc., in Norway), the relatively great difference in the value of forest output between the two countries is really due to better silviculture and management, more access to the interior of forests, advanced techniques in the more developed forest industries and the high forest conscience of the public in Norway. The forests, which occupy about 25% of his country's area, are a vital part of the life of a Norwegian. The dominating species are the Norway spruce and the Scotch pine, though birch is not uncommon. Natural regeneration has played the more important part hitherto. The most common method of timber transport is flotation. Road building, improving the soil conditions by draining, etc., planting and regeneration, mechanization and the advancement of forest industries are among the important items. Few months' study of Norwegian forestry (from July to September, 1957) in the various forests of Norway hardly makes me an authority to speak about it. However, the following is a summary of the impressions gathered in this short period.